Near future climate projections over the Red River Delta of Vietnam using the regional climate model version 3 - Thanh Ngo-Duc; Quang-Trung Nguyen; Tuan-Long Trinh; Thanh-Hang Vu; Van-Tan Phan; Van-Cu Pham (Universiti Kebangsaan Malaysia, 2012)
This study presents a preliminary attempt to assess future climate conditions in the Red River Delta (RRD) region. Outputs of the Community Climate System Model version 3.0 (CCSM3) are dynamically downscaled using the Regional Climate Model version 3 (RegCM3). Numerical experiments and analysis are realized for the baseline 1980-1999 and the future 2030-2049 periods with the A1B and A2 emissions scenarios. We first examine the capability of the model in simulating the 20 years mean climate. Temperature and precipitation outputs for the baseline period are compared with observations at the 17 selected meteorological stations in RRD. Results show that temperature patterns are fairly well reproduced but with systematic cold biases. Precipitation is also well simulated during winter - spring and largely underestimated during summer - autumn. Estimation of the future changes of temperature and precipitation as compared to those of the baseline period reveals that annual temperature of the 2030-2049 appears to be warmer than the baseline temperature of about 1.4±0.2ºC. Summer temperature is likely to increase faster than winter temperature in the future. We also notice that precipitation generally decreases throughout the RRD region except the future JJA rainfall projected by the A2 scenario.